Impact of Multi-leaf Collimator Parameters on Head and Neck Plan Quality and Delivery: A Comparison between Halcyon™ and Truebeam® Treatment Delivery Systems - Li, Taoran (Cureus, 2018)
Purpose A new dual-layer multi-leaf collimator (MLC) system with several improved characteristics was introduced with the Varian Halcyon™ treatment platform. This study evaluated this new MLC’s impact on head and neck plan quality and delivery efficiency. Methods Nine patients were retrospectively studied with Institutional Review Board (IRB) approval. To compare plan quality between the Halcyon dual-layer MLC and Truebeam® MLC, all patients were replanned with the same prescription and target coverage following the institutional clinical protocol for both platforms and using both intensity modulated radiation therapy (IMRT) or volumetrically modulated arc therapy (VMAT) techniques. Organs-at-risk (OAR) dose-volume histogram (DVH) statistics were compared along with total plan monitor units (MU). To evaluate delivery efficiency, actual beam-on time for five patients’ plans were recorded and compared. To evaluate the impact of MLC performance parameters on plan quality, virtual MLC models were generated by matching Truebeam MLC’s parameters to those of the Halcyon dual-layer MLC both individually and combined. OAR doses were then compared between these virtual MLCs, the Truebeam MLC, and the actual Halcyon MLC. Results Overall the Halcyon dual-layer MLC provided similar plan quality compared to Truebeam MLC for VMAT plans, and improved sparing for majority of the OARs when using IMRT. Paired comparison showed median dose differences in mean doses to the parotids, cochlea, esophagus, and larynx ranged from -0.83 Gy to 0.37 Gy for VMAT, and from -4.79 Gy to -0.04 Gy for IMRT, with negative values indicating improved performance by Halcyon. Despite a slight increase in plan MU, the Halcyon reduced the total beam-on time by 42.8 ± 8.5%. Virtual MLC simulations demonstrated that matching MLC transmission accounted for nearly half of the total dose difference between Halcyon and Truebeam IMRT plans. Conclusion When compared to the Truebeam, the Halcyon’s dual-layer MLC achieved similar plan quality using VMAT, and improved OAR sparing using IMRT, while providing nearly twice as fast treatment delivery. Reduction in MLC transmission is the dominating factor contributing to dosimetric differences in OAR sparing.